Indonesian Archaeobotanic Research Development - Amara, Yasmin Lana; Hidayah, Ati Rati; Alifah; Zahro, Fathimatuz; Ariyanto, Adana Presti (Badan Riset dan Inovasi Nasional, 2023)
The application of archaeobotany has been increasing for the last ten years in Indonesia, especially for studying the prehistoric human occupation. Indonesia has incredible biodiversity in flora, and the application of archaeobotanical methods and techniques is essential for understanding people-plant relationships in the past. It is also able to support and complement archaeological results and interpretations developed from analyses of other types of material culture. This paper examines archaeobotanical research in Indonesia through available published literature. The result demonstrates archaeobotanical analyses strengthen and enhance the interpretations of archaeological data and highlight the biases in the application towards prehistoric sites. Our research suggests that more recent archaeological sites have great potential for the application of archaeobotany. This approach needs to be introduced in the early stages of all project planning and research so that suitable recovery methods can be utilized, and adequate time and finances for analyses are factored in. The availability of facilities, infrastructure, and human resources to analyze archaeobotanical data will bring more opportunities for analyses in this field.